DNA Methylation Reorganization of Skeletal Muscle-Specific Genes in Response to Gestational Obesity - Prats-Puig, Anna; García-Retortillo, Sergi; Puig-Parnau, Miquel; Vasileva, Fidanka; Font-Lladó, Raquel; Xargay-Torrent, Sílvia; Carreras-Badosa, Gemma; Mas-Parés, Berta; Bassols, Judit; López-Bermejo, Abel (Frontiers in Physiology, 2020)
The goals were to investigate in umbilical cord tissue if gestational obesity: 1) was associated with the DNA methylation of skeletal muscle-specific genes; 2) could modulate the co-methylation interactions among these genes. DNA methylation was measured in sixteen pregnant women [8-gestational obesity group; 8-control group] in umbilical cord using the Infinium Methylation EPIC Bead Chip microarray. Differentially methylated CpGs were identified with Beta Regression Models (false discovery rate (FDR)<0.05 and an Odds Ratio>1.5 or <0.67). DNA methylation interactions between CpGs of skeletal muscle-specific genes were studied using data from Pearson correlation matrices. In order to quantify the interactions within each network, the number of links was computed. This identification analysis reported 38 differential methylated CpGs within skeletal muscle-specific genes (comprising 4 categories: contractibility, structure, myokines and myogenesis). The effect of gestational obesity on DNA methylation seems to depend on initial methylation levels: compared to control group, gestational obesity promotes hypermethylation in highly methylated genes and hypomethylation in low methylated genes. According to gene localization, 76% of the CpGs are close to a transcription starting site. Gestational obesity diminishes by 275% the number of total interactions in the co-methylation network. Specifically, intra-gene and inter-gene category interactions decreased by 3.5% and 2.9%, respectively. In conclusion, our study showed a complex interaction between gestational obesity and the epigenetic status of muscle-specific genes in umbilical cord tissue. Additionally, gestational obesity may alter the functional co-methylation connectivity of CpG within skeletal muscle-specific genes interactions, reveling an extensive reorganization of methylation in response to gestational obesity.